2020
DOI: 10.1155/2020/2189084
|View full text |Cite
|
Sign up to set email alerts
|

Combining a Cognitive Concurrent Task with a Motor or Motor-Cognitive Task: Which Is Better to Differentiate Levels of Affectation in Parkinson’s Disease?

Abstract: Introduction. Cognitive decline usually coexists with motor impairment in PD. Multitask settings provide appropriate measures to evaluate the complex interaction between motor and cognitive impairments. The main objective was to analyze which concurrent task, i. e., motor or hybrid motor-cognitive, in combination with a cognitive task better differentiates between PD patients with mild and moderate levels of disease. Methods. Thirty-seven individuals (19 male and 18 female) with idiopathic PD performed dual an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
2
0
0
Order By: Relevance
“…Accordingly, performance in the purely cognitive task (Fluency) in the dual condition was directly influenced by cognitive factors, whereas performance of the cognitive–motor task (which includes tracking, involving following a series of points on a sheet of paper) in the dual condition was more broadly influenced by psychosocial and health factors and age. These results can be interpreted in accordance with those of Pereiro et al [ 42 ], who concluded that the demands involved in hybrid cognitive–motor tasks are better for differentiating levels of disability or frailty.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, performance in the purely cognitive task (Fluency) in the dual condition was directly influenced by cognitive factors, whereas performance of the cognitive–motor task (which includes tracking, involving following a series of points on a sheet of paper) in the dual condition was more broadly influenced by psychosocial and health factors and age. These results can be interpreted in accordance with those of Pereiro et al [ 42 ], who concluded that the demands involved in hybrid cognitive–motor tasks are better for differentiating levels of disability or frailty.…”
Section: Discussionsupporting
confidence: 92%
“…The main finding is that the use of a visuo-motor transformation in a reaching movement better detects the effect of DRT, DBS, and DBS + DRT in comparison with habitual reaching movements. This is consistent with previous findings showing that the addition of a cognitive load to a motor task has greater sensitivity in differentiating mild and moderate disability in PD [ 63 ]. Patients with PD may also have a slower movement speed when external cues are reduced [ 64 ] or to unanticipated external visual targets [ 62 ].…”
Section: Discussionsupporting
confidence: 93%